Validation of a Brief Form of the Supervisory Working Alliance Inventory. (January 2020) - Sabella, Scott A.; Schultz, Jared C.; Landon, Trenton J.
The Supervisory Working Alliance Inventory–Trainee Form (SWAI-T) is among the most frequently used instruments for measuring the quality of supervisor–supervisee relationships within counselor supervision. Although the full-scale SWAI-T instrument has proven utility, there are instances when a shorter form may be useful for research and field applications. The current study used secondary data from a pair of cross-sectional studies to test the utility of a brief form of the SWAI-T in a two-step process: (a) reduction of the SWAI-T based on item analyses from an electronic survey of 87 rehabilitation counselors working in a Western state vocational rehabilitation agency and (b) an initial validation study of the instrument using electronic survey responses from a national sample of 228 rehabilitation counselors working in private rehabilitation. The resultant 5-item scale showed evidence of high internal consistency, convergent validity, and minimal differences in psychometric properties relative to the full-scale instrument. An abbreviated supervisory working alliance scale offers practical advantages for select research purposes and for continuous evaluation of supervisory relationships in field environments.